Enhancement of the tensile strengths of rock and shotcrete by thin spray-on liners. (June 2015) - Mpunzi, P.; Masethe, R.; Rizwan, M.; Stacey, T.R.
Graphical abstract: Highlights: Paper deals with tensile strength enhancement by thin spray-on liners (TSLs). Tensile tests on rock and shotcrete, coated/uncoated with TSLs, are reported. Tensile enhancement is typically ∼30% for brittle rock and >40% for shotcrete. Bending tests on rock beams showed similar strength enhancement. TSLs can significantly enhance excavation stability, and shotcrete strength/ductility. Abstract: Thin spray-on liners (TSLs) have been available for application in mining and civil engineering situations for about 20 years. They were initially used as sealants, but have subsequently been developed as surface support liners. Although they are used in substantial quantities in mines in South Africa and Canada, widespread application for support purposes has been met with some scepticism. Observations from users, however, have indicated that, contrary to this scepticism, TSL support performance was almost always better than expected. A reason for the scepticism is probably a lack of quantification of the benefits. This paper aims to address this lack of data to some extent. It provides quantification of the enhancement of tensile strengths of rock and shotcrete due to the application of TSLs. The quantification was achieved using Brazilian indirect tensile testing, and several commercially available TSL products. Some tests were also carried out on small rock beams using three-point bending. The results show that, depending on the TSL product used, the tensile strength of a strong, brittle rock can be increased by approximately 30%, and that of shotcrete by more than 40%. TSL application on a weak porous sandstone resulted in an early tensile strength reduction, probably due to absorption of moisture. This was not the case with TSL application on shotcrete. Many of the rock support mechanisms provided by sprayed liners depend substantially or completely on the tensile strength contribution of the liner. Hence the data provided in this paper makes a contribution to knowledge, of value in the design of support for excavations in rock.